Environmental Burkholderia cepacia Complex Isolates from Human Infections - Baldwin, Adam (Centers for Disease Control and Prevention, 2007)
Members of the Burkholderia cepacia complex (Bcc), found in many environments, are associated with clinical infections. Examining diverse species and strains from different environments with multilocus sequence typing, we identified >20% of 381 clinical isolates as indistinguishable from those in the environment. This finding links the natural environment with the emergence of many Bcc infections.